"Making windows where there were once walls": Transformation in higher education curricula - Menon, K.; Castrillon, G. (South African Journal of Higher Education, 2019)
As the events across South African campuses in 2015 and 2016 have shown, if there are any meaningful insights into quality and transformation, lessons could be learned from conceptions of madness. The intention is to examine curriculum transformation in South Africa and whether there are lessons to be drawn from other post-colonial environments’ experiences. In order to interrogate curriculum transformation, a shared understanding of the purpose of higher education especially in relation to its transformative potential and value needs to be established. As part of this exploration, how the curriculum has become a key focus area in the pursuit of a transformation agenda will be discussed. Given the perceived centrality of the curriculum, the role of the state in setting and supporting the transformation agenda is examined, as are the components of the system that either drives or inhibits the achievement of effective curriculum transformation.